2010
DOI: 10.3109/15622970903555881
|View full text |Cite
|
Sign up to set email alerts
|

The World Federation of Societies of Biological Psychiatry (WFSBP) Guidelines for the Biological Treatment of Bipolar Disorders: Update 2010 on the treatment of acute bipolar depression

Abstract: Although major advances have been made since the first edition of this guideline in 2002, there are many areas which still need more intense research to optimize treatment. The majority of treatment recommendations is still based on limited data and leaves considerable areas of uncertainty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(130 citation statements)
references
References 213 publications
3
120
0
2
Order By: Relevance
“…Current treatment for depression includes drugs such as selective serotonin reuptake inhibitors, tricyclic antidepressants and monoamine oxidase inhibitors. They are effective and tolerated well but noncompliance due to slow action, low response, and plethora of side effects are generally observed [10][11][12][13][14][15][16][17] . Also they inhibit sexual behavior [18] .…”
Section: (Details On Page 997)mentioning
confidence: 99%
“…Current treatment for depression includes drugs such as selective serotonin reuptake inhibitors, tricyclic antidepressants and monoamine oxidase inhibitors. They are effective and tolerated well but noncompliance due to slow action, low response, and plethora of side effects are generally observed [10][11][12][13][14][15][16][17] . Also they inhibit sexual behavior [18] .…”
Section: (Details On Page 997)mentioning
confidence: 99%
“…The treatment of recurrent depressive episodes, which predominate over manic episodes in the majority of patients,2, 3 is an unmet need in the long‐term treatment of bipolar disorder. Antidepressant efficacy has not been demonstrated for standard antidepressants or typical antipsychotics, either as acute treatments for bipolar depression, or as maintenance therapy for the prevention of depression relapse 4, 5, 6, 7, 8. There is weak evidence for the maintenance efficacy of most mood stabilizers in the prevention of depressive relapse (notably lithium, valproate, carbamazepine),9 and stronger evidence suggesting that lamotrigine may be effective in delaying depressive episode recurrence 10…”
Section: Introductionmentioning
confidence: 99%
“…Although treatment guidelines have commonly recommended maintenance therapy with lamotrigine or quetiapine as first‐line treatments in bipolar disorder patients at risk for depressive episode recurrence,4, 5, 6, 7, 8 there clearly is a need for additional options that are safe, well‐tolerated, and effective for the maintenance therapy of bipolar disorder patients at risk for depression recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, some doubt has been cast on the acute antidepressive efficacy of Li by a meta-analytic review [6] that included recent randomized controlled studies [17], since these effects had been observed in small-sized observational studies with relatively short-term follow-up periods. As a result, the latest guideline by the World Federation of Societies of Biological Psychiatry (WFSBP, 2010) does not recommend Li monotherapy as the first-line treatment in acute bipolar depression [13]. In addition, it has been recently pointed out that Li has only limited and insufficient efficacy in relapse prevention for bipolar disorders, and that there is substantial concern over adverse effects during its long-term use, in a systematic review focusing on maintenance pharmacotherapy for bipolar disorders [7].…”
Section: All-around Mood Stabilizers (Li Qtp Olz) 1 LImentioning
confidence: 99%
“…The therapeutic spectrum of mood stabilizers of different classes is summarized in Table 1 and Fig.1, based on reliable systematic reviews published between 2006 and 2010 [5][6][7][11][12][13][14]. In this chapter, mood stabilizers are classified into one of the following three subtypes based on their characteristic mood-stabilizing properties: 1) all-around mood stabilizers, 2) predominantly antimanic mood stabilizers; and 3) predominantly antidepressive mood stabilizers.…”
Section: Tentative Classification Of Mood Stabilizersmentioning
confidence: 99%